Pensiero e tempo Ricerche sullo storicismo critico: figure, modelli, attualità - CAMBI, Franco (Studi e saggi, 2008)
This book encompasses a profound meditation on the twentieth-century fortunes of historicism as a philosophical model. After a reconstruction of its decline (as a unified and compact philosophical "ism" and as the direct heir of idealism, especially in Italy) and of its persistence as a philosophical style, the volume then penetrates the frontier of the neo-historicisms, probing two of their European faces in the shape of José Ortega y Gasset and Theodor W. Adorno. It then goes on to develop various Italian paths: from Fazio-Allmayer to Garin (and his school) from Dal Pra to Massolo, and up to Preti (was he really an "anti-historicist"?). In all these paths the centrality of historicism and its post-metaphysical aspect are clearly focused, as also in the case of the School of Naples, which now represents the most outstanding and significant heir to such critical (and open) neo-historicism.